The Use of Conceptual Metaphors in Advertising: A Cognitive Approach to Persuasive Language - Malkawi, Abeer, H (Journal of Posthumanism, 2025)
This study examines the role of conceptual metaphors in advertising, their cognitive impact, and their persuasive impact on consumer behavior. That is, it is to examine how the conceptual metaphors shape consumers’ perception and behavior, how consumers use cognitive processes to understand the metaphors, and how imagery metaphors and its meanings interact to strengthen the effectiveness of advertising. The study employs mixed methods including primary and secondary data sources. A questionnaire is constructed, to collect primary data to check participants’ responses when they are exposed to conceptual metaphors through written advertisements. The theoretical framework of the study is composed of secondary sources such as books, articles, and previous studies in Arabic and foreign languages. The results indicate that the conceptual metaphors employed in advertising become more distinct in evoking emotional and cognitive responses in customers, thereby influencing their behavior. The contribution to the understanding of the persuasive language in advertising is made and practical implications for marketers to optimize their communication strategy are offered.